2020
DOI: 10.1177/1753425920971347
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a-5p ameliorates LPS-induced inflammatory injury in human A549 cells and mice via targeting RUNX2

Abstract: In this study, we aim to investigate the role of miR-30a-5p in acute lung injury/acute respiratory distress syndrome (ALI/ARDS) using LPS-induced A549 cells and mice. We found cell viability was significantly declined accompanied by cell apoptosis and cell cycle arrest at G0/G1 phase in LPS-treated A549 cells. MiR-30a-5p was down-regulated by LPS treatment and miR-30a-5p significantly protected A549 cells from LPS-induced injury by increasing cell viability, reducing cell apoptosis, promoting cell cycle progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In addition, microRNA (miR)-297, miR-150 and miR-216a are expressed at low levels in ARDS. These miRs exert protective effects against LPS-induced injury in A549 cells by reducing inflammatory cytokine secretion (17,23,24). The present study reported an excessive production of TNF-α, IL-6 and IL-1β in LPS-treated A549 cells, which was consistent with the findings reported previously.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, microRNA (miR)-297, miR-150 and miR-216a are expressed at low levels in ARDS. These miRs exert protective effects against LPS-induced injury in A549 cells by reducing inflammatory cytokine secretion (17,23,24). The present study reported an excessive production of TNF-α, IL-6 and IL-1β in LPS-treated A549 cells, which was consistent with the findings reported previously.…”
Section: Discussionsupporting
confidence: 93%
“…The data showed that miR-30a-5p mimics effectively restrained excessive autophagy induced by MYOCD knockdown and restored the expression of contractile proteins. It has been reported that miR-30a-5p could inhibit the activation of nuclear factor κB (NF-κB) in many types of cells [ 23 25 ]. NF-κB activation has also been shown to inhibit myocardin expression and myocardin-mediated smooth muscle contractile marker genes [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Li et al, miR-30a-5p inhibits phosphorylation levels of STAT3, JNK, p56 and IκBα. Also, miR-30a-5p ameliorates LPS-induced inflammatory injury in human A549 cells and mice via targeting Runt-related transcription factor 2 (RUNX2) [21].…”
Section: Discussionmentioning
confidence: 99%